2018
DOI: 10.1002/ange.201802890
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of DNA Origami Nanostructures in Low‐Magnesium Buffers

Abstract: DNAo rigami structures have great potential as functional platforms in various biomedical applications.Many applications,h owever,a re incompatible with the high Mg 2+ concentrations commonly believed to be ap rerequisite for maintaining DNAo rigami integrity.H erein, we investigate DNAo rigami stability in low-Mg 2+ buffers.D NA origami stability is found to crucially depend on the availability of residual Mg 2+ ions for screening electrostatic repulsion. The presence of EDTAa nd phosphate ions may thus facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
56
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 41 publications
2
56
0
8
Order By: Relevance
“…A particularly important issue for medicala pplications is their interaction with proteins such as endonucleases, which may degrade the well-defined nanoscale shapes.H erein, fundamental insights into this interaction are provided by monitoring DNase Id igestion of four structurally distinct DNA origami nanostructures (DONs) in real time and at as ingle-structure level by using high-speed atomic force microscopy.T he effect of the solid-liquidi nterface on DON digestioni sa lso assessed by comparison with experiments in bulk solution. [16, 17] Although it has been shown that DONs can survive under low-cation conditions, [18,19] stability studies performedi n serum or cell culture media have yielded somewhat controversial and quite distinct results. [2][3][4][5] In recenty ears, programmable DNA origami nanostructures (DONs) [6][7][8][9][10] have been considered promising candidates for the development of tailored and multifunctional drug-delivery vehicles.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…A particularly important issue for medicala pplications is their interaction with proteins such as endonucleases, which may degrade the well-defined nanoscale shapes.H erein, fundamental insights into this interaction are provided by monitoring DNase Id igestion of four structurally distinct DNA origami nanostructures (DONs) in real time and at as ingle-structure level by using high-speed atomic force microscopy.T he effect of the solid-liquidi nterface on DON digestioni sa lso assessed by comparison with experiments in bulk solution. [16, 17] Although it has been shown that DONs can survive under low-cation conditions, [18,19] stability studies performedi n serum or cell culture media have yielded somewhat controversial and quite distinct results. [2][3][4][5] In recenty ears, programmable DNA origami nanostructures (DONs) [6][7][8][9][10] have been considered promising candidates for the development of tailored and multifunctional drug-delivery vehicles.…”
mentioning
confidence: 99%
“…[11][12][13][14] For therapeutic in vivo applications, the DON vehicles should preferably be compatible with the immunes ystem, resistant to nucleases, have as ufficiently long circulation half-life, and be able to maintain their shape at the ionic strengths of the biological fluids. [16, 17] Although it has been shown that DONs can survive under low-cation conditions, [18,19] stability studies performedi n serum or cell culture media have yielded somewhat controversial and quite distinct results. [16, 17] Although it has been shown that DONs can survive under low-cation conditions, [18,19] stability studies performedi n serum or cell culture media have yielded somewhat controversial and quite distinct results.…”
mentioning
confidence: 99%
See 3 more Smart Citations